Brain Serotonin Receptors and Transporters: Initiation vs. Termination of Escalated Aggression - Takahashi, Aki (2010)
RATIONALE: Recent findings have shown a complexly regulated 5-HT system as it is linked to different kinds of aggression. OBJECTIVE: We focus on (1) phasic and tonic changes of 5-HT and (2) state and trait of aggression, and emphasize the different receptor subtypes, their role in specific brain regions, feed-back regulation and modulation by other amines, acids and peptides. RESULTS: New pharmacological tools differentiate the first three 5-HT receptor families and their modulation by GABA, glutamate and CRF. Activation of 5-HT(1A), 5-HT(1B) and 5-HT(2A/2C) receptors in mesocorticolimbic areas, reduce species-typical and other aggressive behaviors. In contrast, agonists at 5-HT(1A) and 5-HT(1B) receptors in the medial prefrontal cortex or septal area can increase aggressive behavior under specific conditions. Activation of serotonin transporters reduce mainly pathological aggression. Genetic analyses of aggressive individuals have identified several molecules that affect the 5-HT system directly (e.g., Tph2, 5-HT(1B), 5-HT transporter, Pet1, MAOA) or indirectly (e.g., Neuropeptide Y, αCaMKII, NOS, BDNF). Dysfunction in genes for MAOA escalates pathological aggression in rodents and humans, particularly in interaction with specific experiences. CONCLUSIONS: Feedback to autoreceptors of the 5-HT(1) family and modulation via heteroreceptors are important in the expression of aggressive behavior. Tonic increase of the 5-HT(2) family expression may cause escalated aggression, whereas the phasic increase of 5-HT(2) receptors inhibits aggressive behaviors. Polymorphisms in the genes of 5-HT transporters or rate-limiting synthetic and metabolic enzymes of 5-HT modulate aggression, often requiring interaction with the rearing environment.